Pengaruh likuiditas, profitabilitas, leverage, dan ukuran perusahaan terhadap manajemen laba - harti ani, Febru; Hardiyanti, Widhian (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to obtain empirical evidence about the effect of liquidity, profitability, leverage, and firm size on earnings management. The population in this study are Manufacturing Companies listed on the Indonesia Stock Exchange (IDX) from 2018 to 2020. This study uses the observation method to obtain information about a number of data that are considered representative of a particular population. The sample in this study was obtained using a purposive random sampling technique, with the sample in the form of the financial statements of manufacturing companies listed on the Stock Exchange with an annual period (ending December 31) for the 2018-2020 period. Based on the research conducted, the results of this study indicate that partially the liquidity variable has a significant positive effect on earnings management. With increasing liquidity, earnings management will experience a significant increase. Partially, the profitability variable has a significant negative effect on earnings management, with increasing company profitability, it will reduce the value of a company's earnings management. In partial leverage does not have a significant effect on earnings management. Partially, the firm size variable has no effect on earnings management.